Design of hign efficiency buck converters - Toka Koç, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Buck converters are used for battery operated systems which supply a wide current range and very low output voltage ripple even when the input voltage changes by more than two orders of magnitude. The converter has to sustain an excellent power efficiency and be able to support load current switching from 0A to Imax with minimum output voltage ripple. Increasing the power efficiency in a switching buck converter requires decreasing the power losses in both light and heavy load operations. However, the light load efficiency is the major concern since portable systems spend their majority of time in idle mode. This work introduces a novel method for increasing efficiency in buck converter systems by utilizing an adaptive output stage size selection technique which decides on the active number of stage segments by comparing capacitive and resistive losses. It takes into account the input supply voltage variation, operating frequency, gate capacitance, actual RON information and load current and finds optimal stage size to obtain optimal efficiency in a switching converter. This is the only work in the literature which conducts high efficiency in light loads without changing the modulation scheme or frequency of switching converter. Two patent applications have been made throughout this work as US14695492: Method for an Adaptive Transconductance Cell Utilizing Arithmetic Operations and US14712941: High Efficiency DC/DC Converter with Adaptive Output Stage.
Keywords: DC-to-DC converters.